PERNIKAHAN USIA DINI DI KECAMATAN BANGUN PURBA KABUPATEN DELI SERDANG - Surisna Okrianti; Siska Indrayani (Ensiklopedia of Journal, 2023)
According to BKKBN (National Population and Family Planning Board) in 2012, the number of adolescents (16-24 years old) was 64 million (27.6%). According to the Central Bureau of Statistics of North Sumatera the birth rate of babies from young mothers (15-19 years old) was about 33%. The infant death rate in North Sumatera was 40/1,000 life births, and 30%-35% of them had been married in young age. The research used phenomenological qualitative method. This strategy was chosen based on the experience of the married couples. The case was concerned with 5 people who got married in young age. The data were analyzed by grouping people and events according to their characteristics which were in accordance with the category and its chronology. The result of the research showed that some factors which caused marriages by minors in Bangun Purba Sub-district were economic factor, educational factor, and pre-marriage pregnancy factor. Its side-effects were easily jealous and suspicious due to psychological immaturity, family’s economic instability (low income), divorce, and the increase in the risk for pregnancy.